2002
DOI: 10.1021/ja020832s
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the High-Pressure Behavior of As, Sb, and Bi

Abstract: The high-pressure behavior of the heavier group 15 elements As, Sb, and Bi was investigated by means of ab initio density functional calculations employing pseudopotentials and a plane wave basis set. The high-pressure structural sequence of these elements is distinguished by the occurrence of the Bi-III structure, which is a complex, incommensurately modulated, host-guest structure. We approximated this structure by a supercell which reproduced the experimentally established pressure stability ranges of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
62
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 38 publications
21
62
3
Order By: Relevance
“…More recent single-crystal data indicate a pairing of the guest atoms which is even more pronounced [44]. This experimental finding is in excellent agreement with the results of a computational investigation of the bonding properties of Bi and Sb where for the fully relaxed structure a pair-formation is evidenced [80]. Finally, at pressures above 28 GPa, antimony forms a cubic body centred modification [81].…”
Section: Antimony and Bismuth (Pentels)supporting
confidence: 86%
See 2 more Smart Citations
“…More recent single-crystal data indicate a pairing of the guest atoms which is even more pronounced [44]. This experimental finding is in excellent agreement with the results of a computational investigation of the bonding properties of Bi and Sb where for the fully relaxed structure a pair-formation is evidenced [80]. Finally, at pressures above 28 GPa, antimony forms a cubic body centred modification [81].…”
Section: Antimony and Bismuth (Pentels)supporting
confidence: 86%
“…The low-pressure modification with an arsenic-type structure transforms at 2.5 GPa to the strongly distorted variant of a primitive cubic structure labelled as Bi-II [82]. Already at the slightly higher pressure of 2.8 GPa there is a structural reorganisation into the phase Bi-III which is -in contrast to the findings of earlier investigations [83][84][85] -characterized by an incommensurate crystal structure [74] with CN close to 9 [80]. The arrangement is very similar to that found for highpressure allotropes of the alkaline-earth metals strontium and barium or that of the lighter homologue antimony.…”
Section: Antimony and Bismuth (Pentels)contrasting
confidence: 64%
See 1 more Smart Citation
“…51 concluded at a phase transition to the cP 1 structure at V ≤ 52Å 3 (incorrect), but found out that "the axial ratio converges to c/a √ 6 before the parameter u converges to u = 1/4" (correct). Another, more recent, calculation 28 concluded that the A7 → Sb-II transition takes place at P = 8.6 GPa, i.e. before the (hypothetical) A7 → cP 1 transformation might occur at the (calculated) pressure of P = 10.7 GPa.…”
Section: Appendix: A7 Structure Optimizationmentioning
confidence: 99%
“…6,9,28,51 An interesting problem had been the question of the existence of a cubic primitive (cP 1) structure of Sb at pressures between 6 and 9 GPa. The cP 1 structure can be viewed as a special case of A7 with u = 0.25 and c/a = √ 6.…”
Section: Appendix: A7 Structure Optimizationmentioning
confidence: 99%